Answer:
Solve by factoring.
1. 2x^2+9x+26=-4x+5
2x²+9x+4x+26-5=0
2x²+13x+21=0
doing middle term factorization
2x²+7x+6x+21=0
x(2x+7)+3(2x+7)=0
(2x+7)(x+3)=0
either
x=-7/2
or
x=-3.
2.
3x^2-6x-4=0
comparing above equation with ax²+bx+c=0
we get
a=3
b=-6
c=-4
By using quadratic equation
x=[tex] \frac{ - b±\sqrt{ {b}^{2} - 4ac } }{2a} [/tex]
Substituting value
x=[tex] \frac{ 6±\sqrt{ {-6}^{2} - 4*3*-4 }}{2*-4} [/tex]
x=[tex] \frac{ 6±\sqrt{ {84}}}{-8} [/tex]
x=[tex] \frac{ 6±2\sqrt{ {21}}}{-8} [/tex]
-8x=6±2√21
taking positive
-8x=6+2√21
x=[tex] \frac{6+2√21}{-8} [/tex]
x=-[tex] \frac{3+√21}{4} [/tex]
taking negative
-8x=6-2√21
x=[tex] \frac{6-2√21}{-8} [/tex]
x=-[tex] \frac{3-√21}{4} [/tex]